2022
DOI: 10.3390/metabo12060496
|View full text |Cite
|
Sign up to set email alerts
|

Ratios of Acetaminophen Metabolites Identify New Loci of Pharmacogenetic Relevance in a Genome-Wide Association Study

Abstract: Genome-wide association studies (GWAS) with non-targeted metabolomics have identified many genetic loci of biomedical interest. However, metabolites with a high degree of missingness, such as drug metabolites and xenobiotics, are often excluded from such studies due to a lack of statistical power and higher uncertainty in their quantification. Here we propose ratios between related drug metabolites as GWAS phenotypes that can drastically increase power to detect genetic associations between pairs of biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
(57 reference statements)
2
1
0
Order By: Relevance
“…Thus, for the three enzymes that should be inhibited in the periphery to boost l -DOPA therapy efficacy, we predict that paracetamol, NAPQI, or both will inhibit two of them (COMT and tyrosinase) while leaving the third (DDC) uninhibited and 3-hydroxyparacetamol will inhibit COMT (in agreement with experimental studies).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Thus, for the three enzymes that should be inhibited in the periphery to boost l -DOPA therapy efficacy, we predict that paracetamol, NAPQI, or both will inhibit two of them (COMT and tyrosinase) while leaving the third (DDC) uninhibited and 3-hydroxyparacetamol will inhibit COMT (in agreement with experimental studies).…”
Section: Resultssupporting
confidence: 93%
“…Paracetamol, 3-hydroxyparacetamol, l -DOPA, and DOPAC also form strong attractive interactions with asparagine. The strong attraction of 3-hydroxy-paracetamol for the COMT active site is in agreement with the experimental observations of Thareja et al 36 In their work they found that 3-methoxyparacetamol is produced in the location of the COMT enzyme; this molecule is made from 3-hydroxyparacetamol, suggesting that it is a substrate for COMT. For tyrosinase, both paracetamol and NAPQI have EBEs within 14% of that of the natural substrate l -DOPA, so they should both be competitive inhibitors for that active site.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation